The capacity to designate a surrogate is distinct from decisional capacity: normative and empirical considerations. Issue 3 (19th February 2021) - Navin, Mark; Wasserman, Jason Adam; Stahl, Devan; Tomlinson, Tom
Abstract : The capacity to designate a surrogate (CDS) is not simply another kind of medical decision-making capacity (DMC). A patient with DMC can express a preference, understand information relevant to that choice, appreciate the significance of that information for their clinical condition, and reason about their choice in light of their goals and values. In contrast, a patient can possess the CDS even if they cannot appreciate their condition or reason about the relative risks and benefits of their options. Patients who lack DMC for many or most kinds of medical choices may nonetheless possess the CDS, particularly since the complex means-ends reasoning required by DMC is one of the first capacities to be lost in progressive cognitive diseases (eg, Alzheimer's disease). That is, patients with significant cognitive decline or mental illness may still understand what a surrogate does, express a preference about a potential surrogate, and be able to provide some kind of justification for that selection. Moreover, there are many legitimate and relevant rationales for surrogate selection that are inconsistent with the reasoning criterion of DMC. Unfortunately, many patients are prevented from designating a surrogate if they are judged to lack DMC. When such patients possess the CDS, this practice is ethically wrong, legally dubious and imposes avoidable burdens on healthcare institutions.